Synthesis of β-oxopropylcarbamates in a recyclable AgBr/ionic liquid catalytic system: An efficient assembly of CO2 under ambient pressure; Journal of CO2 Utilization; Vol. 27 - Song Dandan; Lia Di; Xiao Xuan; Cheng Chen; Chaemchuen S. Somboon; Yuan Ye; Verpoort F. V. K. Frensis Valter Kornelius (2018, 2018)
Title screen